Schwingungseigenschaften der Tetrahalogenooxotechnetate (V) - Baran, Enrique José (1983)
A complete assignment of previously reported vibrational spectra of the TcOX₄ (X = CI, Br, I) anions is proposed. Based on this assignment, force constants and mean amplitudes of vibration are evaluated and the most prominent aspects of the vibrational behaviour and structural characteristics of these species are discussed.